Strategi Pemasaran Unit Usaha Pada Badan Usaha Milik Desa (BUMDES) Di Desa Sikara Tobata Kecamatan Sindue Tobata Kabupaten Donggala - Moh. Qadril Lasaib; Asngadi Asngadi; Harnida Wahyuni Adda (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
BUMDes Sintuvu is a business institution that handles services, which was established in 2017, providing various types of services such as hand tractor rentals, pick-up car rentals, and rental of tunnel tents, chairs, reception tables, and wedding stages. The purpose of this research is to find a new marketing strategy for BUMDes Sintuvu Sikara Tobata Village. This research is a qualitative research. Methods of data collection through interviews and documentation. The result of this study is a marketing strategy through the marketing mix using the 4P’s (Product, Price, Place, Promotion). Conclusion The products/services of Sintuvu BUMDes were chosen so that the products implemented facilitate the needs of the community and do not compete with the community, Sintuvu BUMDes provide the best service to be accepted by the community and satisfying service.